Sustainability reporting in family versus non-family firms: the role of the richest European families - Palma, M. (2018)
The purpose of this study is to compare the sustainability reporting practices of family firms with those of their non-family counterparts and to examine the role of social visibility and reputation. The empirical analysis relies on the 84 firms controlled by one of the European billionaires listed in the Forbes’ 2015 World’s Billionaires Ranking. After controlling for several variables, our findings are consistent with the argument that family firms attach greater importance to sustainability reporting. However, we do not find evidence that within the family firms’ arena those with greatest exposure to reputational damage attribute greater importance to sustainability reporting. We do however find evidence that within firms that attach lower prominence to sustainability issues, family firms, especially those controlled by billionaires, are less likely to present detailed sustainability information in their websites, via autonomous sustainability reports.